2020
DOI: 10.3390/cancers12040844
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Aflibercept in Metastatic Colorectal Cancer: A Literature Review and Expert Perspective on Clinical and Real-World Data

Abstract: Background: Metastatic colorectal cancer (mCRC) represents a substantial health burden globally and an increasing challenge in Asian countries. Treatment options include chemotherapy plus a vascular endothelial growth factor (VEGF) inhibitor (such as bevacizumab, aflibercept or ramucirumab), or anti-epidermal growth factor receptor (EGFR) therapies. Aflibercept, a recombinant fusion protein, has been approved for treatment of mCRC in combination with FOLFIRI for patients whose disease progresses during or afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 52 publications
(66 reference statements)
2
12
0
Order By: Relevance
“…Several retrospective and real-world studies in mCRC patients receiving FOLFIRI-aflibercept have been performed in Spain ( 111 117 ), France ( 118 120 ), the USA ( 121 ) and Asia ( 122 126 ). Its safety profile described in these registry and real-world studies was consistent with those reported in clinical trials; even grade ≥3 AE rates were lower in the real-life population (neutropenia: 7.7–16.2%, fatigue 6–18%, hypertension 5.6–8%), although this finding might be related to underreporting or to an improved management of patients and AEs ( 127 ). The Aflibercept Safety and health-related Quality-of-life Program (ASQoP) (NCT01571284) was a global, multicenter, single-arm, open-label study evaluating the safety and health-related QoL (HRQoL) of FOLFIRI-aflibercept in mCRC patients previously treated with an oxaliplatin-containing regimen.…”
Section: Focus On Afliberceptsupporting
confidence: 76%
“…Several retrospective and real-world studies in mCRC patients receiving FOLFIRI-aflibercept have been performed in Spain ( 111 117 ), France ( 118 120 ), the USA ( 121 ) and Asia ( 122 126 ). Its safety profile described in these registry and real-world studies was consistent with those reported in clinical trials; even grade ≥3 AE rates were lower in the real-life population (neutropenia: 7.7–16.2%, fatigue 6–18%, hypertension 5.6–8%), although this finding might be related to underreporting or to an improved management of patients and AEs ( 127 ). The Aflibercept Safety and health-related Quality-of-life Program (ASQoP) (NCT01571284) was a global, multicenter, single-arm, open-label study evaluating the safety and health-related QoL (HRQoL) of FOLFIRI-aflibercept in mCRC patients previously treated with an oxaliplatin-containing regimen.…”
Section: Focus On Afliberceptsupporting
confidence: 76%
“…Additional options independent of the KRAS mutational status are based on the VEGFR-2 targeting antibody ramucirumab or the VEGF inhibitor aflibercept. Aflibercept has been approved for treatment of mCRC in combination with FOLFIRI, a chemotherapeutic regimen including folic acid, 5-fluorouracil, and irinotecan, for patients whose disease progresses during or after treatment with an oxaliplatin-containing regimen [21]. Ziv-aflibercept is approved for the treatment of mCRC; its molecular structure is the same as that of aflibercept [22].…”
Section: Current Therapiesmentioning
confidence: 99%
“…Thyroid cancer is one of the main indications of VSP inhibitors (VEGFR-TKIs) because VEGF contributes to the occurrence and progression of thyroid malignancy greatly. However, CTs have demonstrated that VEGFR-TKIs can cause adverse events such as thyroid dysfunction (hyperthyroidism and hypothyroidism), with serious consequences that may require discontinuation of VEGFR-TKI therapy [26]. Especially, thyroid dysfunction induced by VEGFR-TKIs may be related to cancer prognosis [27].…”
Section: Mabs Targeting Vegfmentioning
confidence: 99%
“…The number of patients with metastatic colorectal cancer (mCRC) is expected to increase 60 % by 2030, reaching over 2.2 million new patients and 1.1 million deaths, which will definitely pose a tremendous health burden worldwide [26]. Although anti-angiogenesis is a valid anti-cancer strategy in most cases, some VEGFR-TKIs such as sorafenib and sunitinib performed only limited clinical benefits in the treatment of mCRC [26].…”
Section: Mabs Targeting Vegfmentioning
confidence: 99%
See 1 more Smart Citation